EFEKTIFITAS PENERAPAN TEKNIK TOKEN ECONOMY TERHADAP PENINGKATAN DISIPLIN ANAK USIA 5-6 TAHUN DI TK SYAKHSHIYATUL UMMAH KECAMATAN SIAK HULU KABUPATEN KAMPAR - Rambe, Trisnawati Rambe; Risma, Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Based on the results of field observations to discipline students is still low and teachers still use learning methods that dominate and not varied. So that should be the application of the technique token economy. This study aims to determine the effectiveness of the application of the technique token economy to discipline children aged 5-6 years in TK Syakhshiyatul Ummah Siak Upstream Subdistrict Regency Of Kampar. The sample used in this study 20 people. The data collection techniques were used that observation. Data were analyzed using t-test using SPSS 17.0. Research hypothesis is that there is a very significant influence on the discipline of the students after applying the technique token economy. It can be seen from the analysis of data obtained t = 13.330 and p = 0.000. Because p < 0.05, it can be concluded that there are differences in discipline very significant protégé after using a token economy in learning techniques. So it means that Ho is rejected and Ha accepted which means there is a very significant difference between before and after the experiment by applying the technique token economy. Keyword : Discipline, Token Economy